Low vision services for vision rehabilitation in the United Kingdom. Issue 7 (1st July 2002) - Culham, L E; Ryan, B; Jackson, A J; Hill, A R; Jones, B; Miles, C; Young, J A; Bunce, C; Bird, A C
Abstract : Aim: Little is known about the distribution and methods of delivery of low vision services across the United Kingdom. The purpose of this study was to determine the type and location of low vision services within the UK. Methods: Survey by means of a 29 point postal questionnaire, followed when necessary by a five point telephone questionnaire. All known potential providers of low vision services (n = 2539) including hospitals (n = 277), optician/optometry practices (n = 1683), social services (n = 177), voluntary groups (n = 190), specialist teachers (n = 205), and universities (n = 6) were surveyed. For each service provider, the type, magnitude, and geographical location were determined. The distribution of services across the United Kingdom and the ratio of providers to population density of people with a visual impairment were mapped using the Geographic Information System (GIS). Results: Data were obtained on 1945 (77%) service providers: 1679 (66%) responded to the postal questionnaire and 266 (11%) to the telephone questionnaire. Of all respondents, 59% (n = 1135) offer some form of help to people with a visual disability, of which 26% (n = 497) only sell magnifiers and 33% (n = 638) provide low vision services. It is estimated that in total just under 155 000 low vision consultations are offered annually, the bulk of which are provided by hospital eye departments. The distribution was geographically uneven and there appears to be scarcity in some areas. Conclusion: When compared to the probable number of people with a visual impairment in the UK there are apparent inadequacies in service provision in terms of distribution, magnitude, and coordination. The results highlight a need to review current services.